Renoprotective Effect of Formononetin by Suppressing Smad3 Expression in Db/Db Mice - Lv J (Dove Medical Press, 2020)
Jiawei Lv,1 Kai Zhuang,1 Xiyu Jiang,1 Heqing Huang,1,2 Shijian Quan1 1Department of Pharmacology, School of Pharmaceutical Sciences, Guangzhou University of Chinese Medicine, Guangzhou 510006, People’s Republic of China; 2Laboratory of Pharmacology & Toxicology, School of Pharmaceutical Sciences, Sun Yat-Sen University, Guangzhou 510006, People’s Republic of ChinaCorrespondence: Heqing Huang; Shijian QuanDepartment of Pharmacology, School of Pharmaceutical Sciences, Guangzhou University of Chinese Medicine, No. 232 East Wai Huan Road, Guangzhou 510006, People’s Republic of ChinaTel +86 1 392 211 9719Email huangheq@mail.sysu.edu.cn; quansj@gzucm.edu.cnPurpose: Glomerular sclerosis and renal interstitial fibrosis are the most important pathologies in the development of kidney damage under diabetic conditions. Smad3 plays antagonistic roles in high glucose-induced renal tubular fibrosis, which is an important treatment target for diabetic nephropathy (DN). Formononetin (FMN) has multiple effects on diabetic vascular complications including DN. However, whether it plays an anti-fibrosis role by regulating smad3 is unclear. The purpose of this study was to evaluate the renoprotective effect of FMN by suppressing smad3 expression in db/db mice.Methods: FMN was orally administered to db/db mice with a dose of 25 or 50 mg/kg/day for 8 weeks. At the end of the study, serum, urine, and kidney samples were collected for biochemical and pathological examinations. The expressions of proteins and mRNA associated with renal fibrosis were determined by biochemical, histological, immunofluorescence, and real-time PCR analysis.Results: The results showed that FMN substantially improved the glucolipid metabolism, reduced the oxidative stress, and protected renal function in db/db mice. Meanwhile, protein and mRNA expression of smad3 and related regulatory factor of extracellular matrix deposition were significantly suppressed.Conclusion: The present study suggested that FMN has a good renoprotective effect in DN, which plays an anti-fibrosis role in db/db mice by suppressing the expression of smad3.Keywords: formononetin, diabetic nephropathy, db/db mice, renal fibrosis, expression of smad3, antioxidants